A pixação na paisagem de São Paulo: o risco com o construção do sentido da vida urbana - Altamirano, Micaela (2018)
The following research aims to investigate which meaning-effects are produced from the massive presence of a visual manifestation denominated pixação (written with “x”) on buildings and monuments of São Paulo’s contemporary scenery. The general objective of the research is to understand which values are articulated in this cipher, which reveal ways of being and happening in the city, in syncretic construction with the urban space that presents the inequalities and discontinuities produced over the years of the city’s development. Considering the most relevant studies about Pixação, mainly in the study fields of sociology, urbanism and communication, we intend to detail a deepen the understanding of this manifestation from a unexplored perspective: how theirs ways of presence build new senses in the public space. The study corpus, which focuses the space analysis, embraces Sé and República boroughs,in São Paulo’s central area, which maintains the diachronic marks of its construction. To present and analyze the tactics engaged by pixadores, we collect empirical data, news from digital and printed media and videos produced by themselves. Analysing the communicational and identity processes built in the space occupied by pixação, we get in on how the manifestations correlate a part and the whole of the city, approaching the way they make the observer feel the risks and the interactions that the practice of pixação promotes, inviting to enter into their joints and build their senses together. The study is based on the theoretical premises of the discursive semiotics proposed by Algirdas Julien Greimas, with methodological procedures of meaning-generating methods, as well as Eric Landowski’s sociosemiotcs in the formulation of regimes of meaning, interaction and risk, and the postulates of Ana Claudia de Oliveira, especially regarding to semiotics of visuality. The result puts us in front of a visual manifestation of strong aesthetic value which translates the ways of living in the city from the perspective of a peripheral population, which is often marginalized, and start to compose a enunciate of the public spaces with the memory of individual and collective paths in the narratives of the city. Appropriating of the center of the megalopolis, this peripheral population reinscribes themselves as protagonists, re-signifying their invisible place in history. The research contributes, for the analysis about strategies of democratization and appropriation of public space and its patrimony